eGovernment as a Carrier of Context - RICHARD HEEKS (iGovernment Working Paper Series 15, 2004)
eGovernment is a global project of technology transfer, taking designs from one context into a different context. This transfer may take place from country to country or, more subtly, from one group to another. This paper focuses on the former type, using examples of 'e-transparency' projects. But it offers insights into all types of e-government project. The insights suggest a complex interweaving between technology and context. We find that the context of design is inscribed into e-government systems in both explicit and implicit ways. These design inscriptions can mismatch the context of deployment/use, creating a contextual collision that can often lead to e-government failure. In other cases, though, there is some form of accommodation between the two contexts: users may appropriate inscribed elements to their own purposes, or there may even be a reciprocating accommodation between contexts leading to a viable system. Factors that shape these outcomes - either failure or accommodation - are identified, as are the networks of interests that determine the design inscription and deployment accommodation processes. Conclusions are drawn about policy on e-government project design and development of e-government capacities; and about the value of knowledge-building for e-government from developing/transitional economy cases and from the literature on sociology of technology.